Self-defense: Deflecting Deflationary and Eliminativist Critiques of the Sense of Ownership - Gallagher, Shaun (Frontiers in Psychology, 2017)
I defend a phenomenological account of the sense of ownership as part of a minimal sense of self from those critics who propose either a deflationary or eliminativist critique. Specifically, I block the deflationary critique by showing that in fact the phenomenological account is itself a deflationary account insofar as it takes the sense of ownership to be implicit or intrinsic to experience and bodily action. I address the eliminativist view by considering empirical evidence that supports the concept of pre-reflective self-awareness, which underpins the sense of ownership. Finally, I respond to claims that phenomenology does not offer a positive account of the sense of ownership by showing the role it plays in an enactivist (action-oriented) view of embodied cognition.